Distribuição espaço-temporal e aspectos na dinâmica reprodutiva de Pimelodus endêmicos no Baixo Rio Iguaçu, Paraná, Brasil - Teixeira, Evelin Carina (2016)
This study aimed to evaluate the distribution (structure) existence of spatiotemporal variation in the abundances of two species of endemic fish (Pimelodus britskii and Pimelodus ortmanni) Baixo Iguaçu River and tributaries, as well as evaluating the aspects in the dynamics of reproductive biology of locations and sampling periods. The collections of the species were monthly between September 2013 to March 2015. The data were analyzed and planilhados. Numerical space-time abundances were obtained by CPUE and tested by factorial ANOVA for possible differences in that P. britskii and P. ortmanni significant difference between species. Length classes were established by Sturges method, with different amplitudes between both species, higher volumes in length are relative to P. britskii. The sex ratio analyzed using the chi-square test (x2 0.05 = 3.84) showed higher proportions of females compared to males. The reproductive period was analyzed by the frequency of the maturity stages, gonadosomatic ratio (RGS), condition factor and reproductive activity index (IAR), where the species Pimelodus manifest best bodily conditions, occupying environmentes that provide necessary conditions to perform spawning.